Olam International Singapore: Managing Growth and Business Risks - FOO, See Liang (Institutional Knowledge at Singapore Management University, 2009)
In 2005, Olam International Limited (Olam), a Singapore-based global agri-business trader and supply chain manager complemented its organic growth strategy with mergers and acquisitions (M&A). To build M&A capabilities, Olam developed guidelines for its four business group heads to identify and evaluate businesses for investment, and integrate them to realise targeted synergies.Over the next two years, it acquired 20 to 100 percent stakes in agri-businesses in Australia, New Zealand, China and the United States, and invested over US$200 million. While the organic growth was funded using retained earnings and an initial public offering, Olam issued new shares and convertible bonds to finance these acquisitions. Operating globally, Olam recognised that its business was exposed to numerous risks. It identified risk management as a core competence and built a robust risk management system (RMS).The 2005 strategic shift threw up new challenges for its RMS. The volatility in currency and commodity markets burgeoned Olam's currency risks, outlays for derivative operations, and the drought in Australia affected the top-line and bottom-line contribution from the Australian acquisition to the Group. In 2007, Olam saw the opening up of a new counterparty risk for the Fibre and Wood Products business segment.In March 2008, Olam faced a rating downgrade by Merrill Lynch (ML), which caused a dramatic plunge in its share price. The management of Olam needed to respond to ML's rating downgrade, manage the impact of shift in growth strategy on short-term performance and balance leverage with long-term sustainable growth.